Moderating effects of religiosity in the relationship of workplace spirituality and employee performance: a conceptual analysis - Osman-Gani, Aahad M.; Anwar, Md. Aftab (2014)
Workplace spirituality exists in an organization that recognizes employees’ inner feelings of work experience, and helps to nurture it by providing meaningful work environment. Previous research revealed that working in an environment with strong managerial support requires the recognition of working as a higher purpose of life, or spiritual wisdom of individuals than those who do not get pleasure from work. However, like spirituality, religious dedication also plays an important role in people’s lives through shaping their values, knowledge, and attitudes. Various religious groups such as Muslims, Christians, Buddhists, and others with several orientations have differing beliefs. These religious beliefs and commitments influence the feelings and attitude of people towards their job behaviour (Jamal, 2003). Although some work has been done on spirituality in the western hemisphere, very limited empirical study was found to have conducted in Asian context. Osman-Gani, Hashim & Ismail (2013) recently compared the effects of spirituality and religiosity on employee performance, and found religiosity has more effects than religiosity. Findings from such studies will make significant contributions towards advancing the current knowledge base of spirituality, religiosity and employee performance development. The paper will also propose a conceptual framework on the nature of relationship existing between spirituality and employee performance moderated by religiosity and demographics factors (such as age, gender, education etc.) of employees. These may trigger more research interests for conducting empirical studies in the future.